Preparation and Evaluation of Atenolol Floating Beads as a Controlled Delivery System - Lena M. Thomas; Yehia I. Khalil (College of Pharmacy University of Baghdad, 2017)
This study aims to encapsulate atenolol within floating alginate-ethylcellulose beads as an oral controlled-release delivery system using aqueous colloidal polymer dispersion (ACPD) method.To optimize drug entrapment efficiency and dissolution behavior of the prepared beads, different parameters of drug: polymer ratio, polymer mixture ratio, and gelling agent concentration were involved.The prepared beads were investigated with respect to their buoyancy, encapsulation efficiency, and dissolution behavior in the media: 0.1 N HCl (pH 1.2), acetate buffer (pH 4.6) and phosphate buffer (pH 6.8). The release kinetics and mechanism of the drug from the prepared beads was investigated.All prepared atenolol beads remained floating on 0.1 N HCl (pH 1.2) medium over 24 hours. Besides, high yield beads of 73.07- 84.31% was obtained. Encapsulation efficiencies were in the range of 33.10 % -79.04 %, and were found to increase as a function of increasing drug: polymer mixture ratio and the gelling agent concentrations.Moreover, atenolol release profile from the beads was affected by the pH of the dissolution medium. It was found to be slowest in 0.1 N HCl (pH 1.2) and fastest in phosphate buffer (pH 6.8).The obtained results suggest that atenolol could be formulated as a controlled release beads, using ethylcellulose and alginate as polymers, using ACPD method. Keywords: Floating beads, Atenolol, Controlled Delivery System.